Educational workshops about arterial hypertension - a quasi-experimental study - Rafaella Pessoa Moreira; Nirla Gomes Guedes; Tahissa Frota Cavalcante; Viviane Martins da Silva; Thelma Leite de Araujo (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2005)
The study aims to describe the development and the workshops evaluations focusing in the educational actions about arterial hypertension, which happened with two hundred and two students in a public school in Fortaleza-Ceará, in 2003. The workshops organization happened in three stages: modeling, application and evaluation. The modeling stage comprehended the elaboration of the workshops that were put in practice in the application phase. In the evaluation stage, it considered the knowledge obtained by the school in the workshops. It concluded that the materials used were the instruments adequated in the educational development in health.